The political economy of everyday life in Africa : beyond the margins - Adebanwi, Wale; Ferguson, James, 1959- (James Currey, 2017)
What are the fundamental issues, processes, agency and dynamics that shape the political economy of life in modern Africa? In this book, the contributors - experts in anthropology, history, political science, economics, conflict and peace studies, philosophy and language - examine the opportunities and constraints placed on living, livelihoods and sustainable life on the continent. Reflecting on why and how the political economy of life approach is essential for understanding the social process in modern Africa, they engage with the intellectual oeuvre of the influential Africanist economic anthropologist Jane Guyer, who provides an Afterword. The contributors analyse the political economy of everyday life as it relates to money and currency; migrant labour forces and informal and formal economies; dispossession of land; debt and indebtedness; socio-economic marginality; and the entrenchment of colonial and apartheid pasts.